Pengaruh Return On Asset (ROA), Debt To Equity Ratio (DER), dan Debt To Asset Ratio (DAR) Terhadap Harga Saham pada Perusahaan Sektor Healthcare yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Bambang Susilo; Kumba Digdowiseiso; Clarissa Alexandra (Syntax Literate, 2022)
This study aims to determine the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and Debt to Assets Ratio (DAR) on Stock Price in Healthcare sector companies listed on Indonesia Stock Exchange fot the 2016-2020 period. The population of this study includes 23 health sector companies lised on Indonesia Stock Exchange in 2016-2020. The sampling technique was purposive sampling and obtained as many as 13 companies. This study uses secondary data on the form of financial statements that meet the criteria, data obtained from the Indonesia stock exchange website which can be accessed through www.idx.co.id. Data analysis using the STATA 16 computer program. The results of this study indicate that the Return on Assets variable has a positive and significant effect on stock price of health sector companies. The variable Debt to Equity Ratio and Debt to Assets Ratio have a negative and insignificant effect on stock prices of health sector companies.